2013
DOI: 10.1103/physrevd.88.104040
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the equation of state of nuclear matter with gravitational wave observations: Tidal deformability and tidal disruption

Abstract: We study how to extract information on the neutron star equation of state from the gravitational wave signal emitted during the coalescence of a binary system composed by two neutron stars or a neutron star and a black hole. We use Post-Newtonian templates which include the tidal deformability parameter and, when tidal disruption occurs before merger, a frequency cut-off. Assuming that this signal is detected by Advanced LIGO/Virgo or ET, we evaluate the uncertainties on these parameters using different data a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 57 publications
(127 reference statements)
0
50
0
Order By: Relevance
“…Understanding the magnitude of these two sources of error is the core motivator of this work. Several studies have used the Fisher information matrix (FM), which is only valid in the large signal-to-noise ratio (SNR) limit, to estimate the measurability of tidal effects on the CBC gravitational waveform [10][11][12][15][16][17][18]. Flanagan and Hinderer [10] were among the first to show that advanced detectors can constrain the tidal influence of NSs on the early inspiral portion of the CBC waveform.…”
Section: Background and Motivationmentioning
confidence: 99%
“…Understanding the magnitude of these two sources of error is the core motivator of this work. Several studies have used the Fisher information matrix (FM), which is only valid in the large signal-to-noise ratio (SNR) limit, to estimate the measurability of tidal effects on the CBC gravitational waveform [10][11][12][15][16][17][18]. Flanagan and Hinderer [10] were among the first to show that advanced detectors can constrain the tidal influence of NSs on the early inspiral portion of the CBC waveform.…”
Section: Background and Motivationmentioning
confidence: 99%
“…What level of numerical approximation and how many macroscopic observable data points are needed to achieve reasonable levels of accuracy for "realistic" neutron-star equations of state? A number of researchers have studied various observational and data-analysis questions associated with the inverse stellar structure problem, both in the context of using mass and radius observations [15][16][17][18][19], and in the context of using mass and tidal deformability measurements from gravitational-wave observations [3][4][5][6][7][8][9][10][11][12][13][14]. To our knowledge, our studies of the more fundamental questions about solving the inverse stellar structure problem described in our papers are unique.…”
Section: Introductionmentioning
confidence: 97%
“…This may turn out to be the case, but the spectral approach for solving this problem does not (in principle) depend very strongly on exactly which observables are used. Recent work [3][4][5][6][7][8][9][10][11][12][13][14] has shown that gravitational-wave observations of binary neutron-star mergers should provide accurate measurements of the masses and tidal deformabilities of neutron stars once the advanced LIGO-VIRGO network of detectors becomes operational (within the next few years). The possibility of using this type of observational data to solve the inverse stellar structure problem is explored in Sec.…”
Section: Introductionmentioning
confidence: 99%
“…Measuring the NS deformability through GW detections would help to constrain the behavior of matter at ultranuclear density 18,[37][38][39][40] . This has motivated a vast literature on the tidal deformability of nonspinning NSs.…”
Section: Tidal Deformations Of Spinning Nssmentioning
confidence: 99%
“…On the one hand a deeper theoretical understanding of the tidal deformability within general relativity is highly desirable, because the nonlinearities of the theory introduce some subtleties in the definition of the tidal Love numbers 1,2 for relativistic compact objects 3,4 . On the other hand, the first direct detection of gravitational waves (GWs) by aLIGO 5 , the prospects of measuring the tidal Love numbers through GW detections of compact binaries [6][7][8][9][10][11][12][13][14][15][16][17][18] , and the related possibility of constraining the equation of state (EoS) of neutron stars (NSs) through GW astronomy, make it urgent to include spin-tidal effects in the gravitational waveforms. In this work we briefly review some recent results on the deformability and tidal Love numbers of spinning black holes (BHs) and NSs.…”
Section: Introductionmentioning
confidence: 99%